2018
DOI: 10.3126/jaar.v4i2.19534
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Drug Abuse In Youth: Case of Mid-Western Region of Nepal

Abstract: Drug abuse is one of the serious social problems in Nepal and elsewhere for a long time. Drug abuse has several effects over the human life. Burgeoning unemployment, broken family, crime, depression, love failure, formation of peer group, mass media are major problems faced by the youth of the country. This paper explores the causes of drug abuse among youth in Mid-Western Region of Nepal. Quantitative research method was used to draw the data from 252 respondents. Simple random sampling technique was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…It was perhaps no surprise that peer groups appeared to play a very influential role for the initiation and continued use of psychoactive substances, especially among youths, given previous studies conducted in Nepal and other countries showed the influence of peers to use psychoactive substances [32][33][34][35]. Since adolescents and youth share special bonding rituals with friends, it is easier to be influenced by the behaviors of friends and difficult to reject offers of psychoactive substance use [36].…”
Section: Plos Onementioning
confidence: 99%
“…It was perhaps no surprise that peer groups appeared to play a very influential role for the initiation and continued use of psychoactive substances, especially among youths, given previous studies conducted in Nepal and other countries showed the influence of peers to use psychoactive substances [32][33][34][35]. Since adolescents and youth share special bonding rituals with friends, it is easier to be influenced by the behaviors of friends and difficult to reject offers of psychoactive substance use [36].…”
Section: Plos Onementioning
confidence: 99%
“…A bad family relationship pushed the key informants towards drug addiction. Having bad familial relationships can often lead to drug addiction as an escape from reality due to the relaxing psychological effects of drug use (Pathak & Pokharel, 2017).…”
Section: Subtheme 6: Life Issuesmentioning
confidence: 99%
“…According to this table, there was no significant association of cannabis use with any of the socio demographic profile. 2 This is of great concern as this is the age for shaping career of the individuals for building productive life. In this study, Alcohol was most frequently used by medical students which was 47.75% and among the alcohol users; 32% were harmful users.…”
Section: Association Of Cannabis With Socio Demographic Profilementioning
confidence: 99%
“…Also seen was that the overwhelming majority (95.0%) of the drug users started before 25 years of age. 2 Niraula SR et al 3 reported prevalence of alcohol consumption in 17% of 2340 cluster samples of women of age more than 15 years in Dharan. The burning issue of substance abuse among young people is equally present in medical and dental students.…”
Section: Introductionmentioning
confidence: 99%